Pilomatrix carcinoma of the scalp with pulmonary metastasis: A case report of a complete response to oral endoxan and etoposide - ARSLAN, DENIZ (D.A. Spandidos, 2014)
Pilomatrix carcinoma is an extremely rare skin tumor derived from basaloid cells in the hair follicles; it often exhibits locally aggressive behavior with a tendency toward local recurrence. The average age of occurrence is 45 years, and there appears to be a male to female incidence ratio of 4:1. Although pilomatrix carcinomas are predominantly identified in the neck and scalp, there are studies in the literature reporting other tumor development sites, including the upper extremities, torso and popliteal fossa. If diagnosed at an early stage, this malignant tumor is generally treated with wide surgical resection. However, for the advanced-stage tumors, there are no standard treatment procedures known to produce good results. The current study presents the case of a 76-year-old male with pilomatrix carcinoma originating from the scalp with metastases to the lung. The patient had a rapid and complete clinical response following an oral combination chemotherapy regimen of cyclophosphamide and etoposide.